Peningkatan Unsur Hara Kalium dalam Tanah Melalui Aplikasi POC Batang Pisang dan Sabut Kelapa - Sitti Rahma; Burhanuddin Rasyid; Muh. Jayadi (Universitas Hasanuddin, 2019)
In Indonesia, there is not much use of potassium fertilizer for plants. Generally, farmers are more familiar with nitrogen and phosphorus fertilizers than potassium. This is caused potassium is expensive and hard to find, so there should be another alternative for easily and economic potassium fertilizer. This study aims to analyze the effect of organic liquid fertilizer produced from banana stem and coconut fiber to increase Potassium in soil and maize growth on ex-cassava cultivation land in Moncongloe Bulu Village, Moncongloe District, Maros Regency. The study used randomized block design within two factors and replied for three times. The first factor is coconut liquid fertilizer with 4 levels; SK1 (50 ml/pot), SK2 (100 ml/pot), SK3 (150 ml/pot) and SK4 (200 ml/pot). The second factor is banana liquid fertilizer with 4 levels; BP1 (25ml/pot), BP2 (50ml/pot), BP3 (75ml/pot) and BP4 (100ml/pot), so there are 27 total of treatment units. The results showed that coconut liquid fertilizer significantly affected plant height, number of leaves, dry matter weight, dry root weight, matter weight, root weight, organic carbon, cation exchanged capacity, percentage Potassium of maize, and gained the highest average of Pottassium increasing in soil. Nevertheless, it has not significant effect to soil pH.